CONVENTIONAL AND MOLECULAR STUDY OF Babesia spp. OF NATURAL INFECTION IN DRAGGING HORSES AT SOME AREAS OF BAGHDAD CITY, IRAQ - & et al., Faraj (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The present study was planned to investigate equine babesiosis in dragging horses in Baghdad city, Iraq by using microscopical and molecular (PCR) techniques. 150 blood samples of horses examined for Theileria equi and Babesia caballi. 16.66% (25/150) were positive by microscopic examination. No significant difference was observed in infection rates between male and female horses and among different age groups. The result showed that PCR method has high rate of infection36% (9/25). Nine positive PCR products were sequenced and deposited in Genebank data base for first time in Iraq, phylogenic analysis demonstrated that 5 sequences belongs to T. equi (MK350319, MK346272, MK346273, MK346274 and MK36275), while 4 sequence (MK346276, MK346277, MK346278 and MK350318) belongs to B. caballi, and mounted a low genetic variation 0.035 and 0.05 respectively, among other comparison isolates. In conclusion PCR technique followed by phylogenic tree analysis a reliable methods for epidemiological, diagnosis and identification of genetic variants studies.